2021
DOI: 10.3390/cancers13122857
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G and HLA-E Immune Checkpoints Are Widely Expressed in Ewing Sarcoma but Have Limited Functional Impact on the Effector Functions of Antigen-Specific CAR T Cells

Abstract: Immune-inhibitory barriers in the tumor microenvironment of solid cancers counteract effective T cell therapies. Based on our finding that Ewing sarcomas (EwS) respond to chimeric antigen receptor (CAR) gene-modified effector cells through upregulation of human leukocyte antigen G (HLA-G), we hypothesized that nonclassical HLA molecules, HLA-G and HLA-E, contribute to immune escape of EwS. Here, we demonstrate that HLA-G isotype G1 expression on EwS cells does not directly impair cytolysis by GD2-specific CAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The HLA-E antigen present peptides derived from the leader sequences of HLA-A, -B, -C and -G to inhibitory NKG2A/B or activating NKG2C receptors paired with CD94 and expressed on NK and CD8+ T cells; self- and pathogen-specific HLA-E-restricted cytotoxic CD8+ T cells have been also detected ( 100 ). In Ewing sarcoma, a recent IHC study has reported that 22 out of 26 (85%) pre-treatment tumors were positive for HLA-E expression on tumor cells, infiltrating macrophages, or both; however, HLA-E expression on tumor cells did not impair the preclinical activity of GD2-specific chimeric antigen receptor (CAR) T cells ( 81 ). HLA-E expression has been also reported in adult astrocytoma and GBM, being particularly prominent in pseudopalisades associated with tumor invasion, and protects glioma cells from NKG2D-mediated lysis by NK cells in vitro ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HLA-E antigen present peptides derived from the leader sequences of HLA-A, -B, -C and -G to inhibitory NKG2A/B or activating NKG2C receptors paired with CD94 and expressed on NK and CD8+ T cells; self- and pathogen-specific HLA-E-restricted cytotoxic CD8+ T cells have been also detected ( 100 ). In Ewing sarcoma, a recent IHC study has reported that 22 out of 26 (85%) pre-treatment tumors were positive for HLA-E expression on tumor cells, infiltrating macrophages, or both; however, HLA-E expression on tumor cells did not impair the preclinical activity of GD2-specific chimeric antigen receptor (CAR) T cells ( 81 ). HLA-E expression has been also reported in adult astrocytoma and GBM, being particularly prominent in pseudopalisades associated with tumor invasion, and protects glioma cells from NKG2D-mediated lysis by NK cells in vitro ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether HLA-E and HLA-F expression promotes immune evasion from NK and T cells or contribute to expand the HLA repertoire on tumor cells remains to be established. Of note, HLA-G expression is induced by IFNγ in Ewing sarcoma cell lines, and is detected in a majority of tumor biopsies on both tumor and infiltrating myeloid cells ( 81 , 102 ). In our study, we did not detect HLA-G expression in any PDX by Taqman assay targeting the exon 5-6 boundary present in transcripts encoding membrane-bound HLA-G isoforms, in accordance with an inducible rather than constitutive expression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that allo-SCT is not sufficient for immunotherapy of AES, and novel therapeutic strategies are in urgent demand, such as TCR-based immunotherapy [ 40 ]. CAR T cells have also been developed for AES [ 41 ]. The limitation of this approach is that CARTs can only target membrane molecules.…”
Section: Discussionmentioning
confidence: 99%
“…PDL-1 and PDL-2 expressed on osteosarcoma cells bind to PD-1 expressed on TILs, contributing to immunosuppression and tumor progression ( 65 68 ). In Ewing sarcoma, MHC class I molecule HLA-G is expressed on both tumor cells and tumor-infiltrating lymphocytes ( 69 ). HLA-G is associated with an increased number of TILs and its upregulation can contribute to immune escape ( 70 ).…”
Section: Adaptive Immunitymentioning
confidence: 99%